+0  
 
0
95
2
avatar

In the quadratic equation x^2+((k-(1/k))x-1=0 solve for $x$ in terms of $k$.

 Dec 24, 2019
 #1
avatar+109563 
+1

x^2+((k-(1/k))x-1 = 0

 

To  simplify things, let   [ ( k -1/k ) ] =  [ k^2 - 1 ]  / k  =   a

 

So we have

 

x^2  +  ax  -  1                               complete the square on x

 

x^2  + ax +  a^2/4  =   1  + a^2/4         factor

 

( x + a/2)^2  = 1  + a^2/4         take both roots

 

x +   a/2 =  ±√ ( [ 4 + a^2 ] / 4 ]

 

x  =  ±√[4 + a^2] / 2    -  a/2

 

          ±√ [ 4  + [ k^2 - 1]^2 ]  -  [ k^2 -1]

x =    ______________________________

                                   2k

 

            ±√ [ 4 + k^4 - 2k^2 + 1 ]  - k^2 + 1

x  =   _______________________________

                                     2k

 

          ±√ [ k^4 - 2k^2  + 3 ]  - k^2 + 1

x = ____________________________

                                  2k

 

           

            

 

 

 

 

cool cool cool

 Dec 24, 2019
 #2
avatar
0

\(\displaystyle x^{2}+\left(k-\frac{1}{k}\right)x-1=0,\\ kx^{2}+(k^{2}-1)x-k=0,\\ x=\frac{1-k^{2}\pm\sqrt{(k^{2}-1)^{2}+4k^{2}}}{2k}=\frac{1-k^{2}\pm \sqrt{(k^{2}+1)^{2}}}{2k} =\frac{1-k^{2} \pm (k^{2}+1)}{2k}, \\ x=\frac{1}{k}\text{ or }x=-k.\)

.
 Dec 24, 2019

35 Online Users

avatar
avatar